2007
DOI: 10.1111/j.1365-3040.2007.001689.x
|View full text |Cite
|
Sign up to set email alerts
|

Major diffusion leaks of clamp‐on leaf cuvettes still unaccounted: how erroneous are the estimates of Farquhar et al. model parameters?

Abstract: Estimates of leaf gas-exchange characteristics using standard clamp-on leaf chambers are prone to errors because of diffusion leaks. While some consideration has been given to CO2 diffusion leaks, potential water vapour diffusion leaks through chamber gaskets have been neglected. We estimated diffusion leaks of two clamp-on Li-Cor LI-6400 (LiCor, Inc., Lincoln, NE, USA) leaf chambers with polymer foam gaskets and enclosing either 2 or 6 cm 2 leaf area, and conducted a sensitivity analysis of the diffusion leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
131
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(149 citation statements)
references
References 40 publications
10
131
2
3
Order By: Relevance
“…The applicability of the system for A Ci curve measurement was tested in the sunflower (Helianthus annuus L.) leaf. We took special care to minimize bulk air flow through the leaf (Lauer and Boyer, 1992;Boyer and Kawamitsu, 2011), diffusion leaks (Flexas et al, 2007;Rodeghiero et al, 2007), and changes in the CO2 gradient across the leaf mesophyll (Mott and O'Leary, 1984;Parkhurst et al, 1988;Parkhurst and Mott, 1990) that can be important for the measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of the system for A Ci curve measurement was tested in the sunflower (Helianthus annuus L.) leaf. We took special care to minimize bulk air flow through the leaf (Lauer and Boyer, 1992;Boyer and Kawamitsu, 2011), diffusion leaks (Flexas et al, 2007;Rodeghiero et al, 2007), and changes in the CO2 gradient across the leaf mesophyll (Mott and O'Leary, 1984;Parkhurst et al, 1988;Parkhurst and Mott, 1990) that can be important for the measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most studies of plant metabolic scaling have been based on the aboveground parts and have ignored respiration of the roots, which is very difficult to measure (23). Furthermore, the flow of dissolved CO 2 in the sap brings into question the accuracy of estimating whole-tree respiration based on measuring small portions of large trees using the standard clamp-on chambers that are commercially available (16,(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Furthermore, most studies of plant metabolic scaling have been based on the aboveground parts and have ignored respiration of the roots, which is very difficult to measure (23). Furthermore, the flow of dissolved CO 2 in the sap brings into question the accuracy of estimating whole-tree respiration based on measuring small portions of large trees using the standard clamp-on chambers that are commercially available (16,(27)(28)(29)(30).Given the methodological difficulties inherent in whole-plant physiological studies, it is not surprising that there have thus far been no empirical measurements of complete whole-plant respiration, including roots, that have a reasonable sample size and encompass a wide range of plant sizes (2,22,26,(31)(32)(33)(34). Accurate and efficient methods using whole-plant chambers to measure respiration rates have recently been developed (5,18,19,(24)(25)(26) and can be applied to assess metabolic scaling (Fig.…”
mentioning
confidence: 99%
“…Some studies have proposed that the overestimation of RLL is caused by the CO2 acting as an inhibitor of certain enzymes (Brooks & Farquhar 1985, Kirschbaum & Farquhar 1987, Tjoelker et al 2001. However, a large number of studies suggest that leaf respiration changes with CO2 possibly due to small leaks or diffusion in the gas exchange measurement systems (Amthor et al 2001, Pons & Welschen 2002, Shapiro et al 2004, Flexas et al 2007, Rodeghiero et al 2007. Therefore, in this study RLL was corrected based on the method suggested by Li-Cor Inc (2004) to compensate the CO2 leakage in the Laisk method.…”
Section: Uncertainties In Day Respiration Estimatementioning
confidence: 99%
“…Therefore, the respiration rate measured at low CO2 concentration was generally overestimated. A correction for leakage was necessary because it is hard to avoid CO2 exchange or leakage between the infrared gas analyzer (IRGA) chamber and the surrounding air (Pons & Welschen 2002, Shapiro et al 2004, Flexas et al 2007, Rodeghiero et al 2007). We corrected for CO2 leakage by diffusion in the Laisk method based on the following equation (eqn.…”
Section: Measurements and Data Processingmentioning
confidence: 99%